Analisis Keterampilan Proses Sains Mahasiswa Pendidikan Biologi melalui Kegiatan Praktikum Histologi - Rina Astuti; Annur Indra Kusumadani (Lembaga Pengembangan Kinerja Dosen, 2025)
Histology practicum, as one of the compulsory practicum courses, offers a great opportunity to practice various aspects of science process skills through microscopic tissue observation activities, identification of cell and tissue structures, and analysis of tissue functions in organisms. This study aims to analyze the science process skills biology education students through histology practicum activities. This study uses a quantitative descriptive approach with a survey method to analyze the science process skills of biology education students through histology practicum activities. Data collection in this study used three main techniques, namely science process skills tests, direct observation, and analysis of practicum report documents. Furthermore, the data were analyzed descriptively quantitatively using descriptive statistics to describe the profile of students' science process skills. Analysis per aspect revealed that students had good skills in the aspects of observing (78.50%), classifying (76.33%), interpreting data (71.67%), applying concepts (73.25%), and communicating results (73.40%), which indicates that histology practicum is effective in developing basic science process skills. However, the aspects of formulating hypotheses (58.17%) and planning experiments (54.83%) were still in the sufficient category, indicating that students experienced difficulties in integrated science process skills that require higher-order thinking skills. The findings this study provide important implications for the development of more comprehensive histology practicum learning strategies, including the integration of inquiry approaches, the use of continuous formative assessment, the application of differentiated learning, and strengthening the connection between theory and practice to optimize the development of all aspects of science process skills of prospective biology teachers.